ASSOCIATION NONALCOHOLIC FATTY LIVER DISEASE AND RISK OF HYPERTENSION : A SYSTEMATIC REVIEW - Persson Jeffry, Erick (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Nonalcoholic fatty liver disease (NAFLD) is a common liver disease characterized by fat accumulation in liver cells. It is linked to obesity and insulin resistance. NAFLD increases the risk of cardiovascular complications and liver-related problems, while its association with hypertension is not yet clear. Aim: to investigate the potential link between NAFLD and hypertensionMethods: This qualitative systematic review conducted a comprehensive search on Ovid-MEDLINE up until March 2021 to identify longitudinal observational studies examining the relationship between nonalcoholic fatty liver disease and the development of hypertension, following the guidelines of PRISMA. The study selection included longitudinal studies with a minimum one-year follow-up.Results: Out of the initial 1108 articles, a final analysis of 11 observational cohort studies was conducted after excluding studies based on predetermined criteria, resulting in a total sample size of 390,348 individuals with an average follow-up period of 5.7 years. These studies, conducted in various regions, examined the relationship between NAFLD and incident hypertension using consistent diagnostic methods.Conclusion: NAFLD is linked to a higher risk of hypertension, emphasizing the importance of monitoring and further investigating the impact of NAFLD severity on hypertension.